Effect of Influencer Marketing Strategy On Consumer behaviour In Fast Moving Consumer Goods firms In Ghana - Bansah, Pearl Fafa; Gaffar, Vanessa; Disman, Disman; Yuliawati, Ayu Krishna (ASEAN Marketing Journal, 2023)
Manuscript type: Research paper Research Aims: This study examines the influence of influencer marketing strategies on consumer purchasing behaviour among fast-moving consumer goods (FMCG) companies in Ghana. Design/methodology/approach: This study employs an explanatory (causal) research design. A 31-item questionnaire split into four categories was used to collect quantitative data. An online questionnaire was sent to FMCG consumers in Ghana's Greater Accra and Ashanti Regions, aged 18–48 years and older. Multiple regression analysis was performed to establish relationships between the study variables. Research Findings: The findings showed that YouTube is the most popular social media platform among Ghanaian users, according to the findings of the study. Several factors, such as attractiveness, credibility, expertise, reach, and engagement, affect the influence of Ghanaian influencers on consumer purchasing behaviour in FMCG firms. It has been demonstrated that these factors have a positive and statistically significant effect on the purchasing behaviour of customers Theoretical Contribution/Originality: This study enhances the theoretical understanding of influencer marketing's efficacy and provides valuable insights for practitioners and marketers seeking to leverage influencer marketing to improve their brand's performance in the competitive FMCG market. Practitioner/Policy Implications: This study emphasises the need for strategic and authentic influencer marketing for Ghana's FMCG firms. To increase customer engagement, organisations must carefully identify influencers, emphasise trust and authenticity, improve product-related content, and encourage interactive involvement. Research limitation/implications: The concentration of FMCG firms in Ghana limits the generalisability of the study's findings to other industries or countries